Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

Fox375

  • 3 years ago

If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to y from the first equation is substituted into the second equation. 6x – y = 1 4x – 3y = –11 4(–6x + 1) – 3y = –11 4(6x + 1) – 3y = –11 4x – 3(6x – 1) = –11 4x – 3(–6x – 1) = –11

  • This Question is Closed
  1. AbhimanyuPudi
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    C

  2. AbhimanyuPudi
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    6x-y=1 6x-1=y(Jusy rearrange terms in this way) Substitute this in the second equation... 4x-3(6x-1) = -11

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy